Pembuatan Briket Biorang Dari Limbah Tempurung Kelapa Sawit (Elaeis Guineensis Jacq) Dengan Perekat Tepung Porang - Ayub, Akmal Rizki; Rihayat, Teuku; Zaini, Halim (Politeknik Negeri Lhokseumawe, 2025)
Biorang briquettes are solid fuels derived from a mixture of powder and adhesive to form a specific shape according to the desired results through a pressing process. The purpose of this study was to determine the variation in particle size and carbonization temperature of palm shell waste on the results of biorang briquette testing. This study used two independent variables, namely the particle size of palm shell charcoal 10 mesh, 20 mesh, 40 mesh, 60 mesh and 80 mesh and the carbonization temperature of 4000C, 450 0C, 500 0C, 550 0C and 600 0C. The results showed that the higher the temperature and particle size of palm shell charcoal, the lower the water content, ash content and flame duration, while the volatile content increased with increasing temperature and particle size.